Singapore’s “Global Schoolhouse” Aspirations - Tan, Jason (International Higher Education, 2016)
Singapore’s Trade and Industry Ministry announced an ambitious ‘global schoolhouse’ vision in 2002. This vision, which was clearly economically-driven in nature, involved Singapore capturing a share of the lucrative international education market by attracting 150,000 international full-fee paying students by the year 2015. Fourteen years down the road, it appears that the target is nowhere near attainment.